2018
DOI: 10.1097/md.0000000000009712
|View full text |Cite
|
Sign up to set email alerts
|

The anteroposterior diameter of nodules in the risk assessment of papillary thyroid microcarcinoma

Abstract: This study investigates the application of ultrasound, especially the anteroposterior diameter of nodules in the malignancy and metastasis risk assessment of papillary thyroid microcarcinoma through a retrospective analysis of 500 cases of thyroid nodule ultrasonography.We selected 500 patients with thyroid nodules (maximum nodule diameter ≤2.0 cm) that had been diagnosed clinically and graded TI-RADS 4c by ultrasonography and surgically treated. Among these, there were 258 cases of pathologically diagnosed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(20 reference statements)
0
11
0
Order By: Relevance
“… 10 , 11 Whereas the correlation is reported for the nodules sized less than 1.5 mm and the risk of malignancy. 12 , 13 The current predicted model for thyroid malignancy is based on age, nodule size, and fine-needle aspiration cytopathology. 7 Ideally, surgeons require an algorithm(s) that finds the malignant potential of a nodule preoperatively to reduce unnecessary diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Whereas the correlation is reported for the nodules sized less than 1.5 mm and the risk of malignancy. 12 , 13 The current predicted model for thyroid malignancy is based on age, nodule size, and fine-needle aspiration cytopathology. 7 Ideally, surgeons require an algorithm(s) that finds the malignant potential of a nodule preoperatively to reduce unnecessary diagnostic methods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with lateral cervical lymph node metastasis are frequently at least stage T1N1bM0, and they are more susceptible to recurrence and metastasis than patients with stage T1N1aM0. In addition, the cutoff criterion of the thyroid nodule size in the present study was 0.9 cm, mainly because if the nodule size is >9 mm, its risk of metastasis increases, compared with it risk decreasing if the size is <9 mm (41).…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, Ma et al [15] found that predictors of PTMC included an aspect ratio > 1, apparent hypoechogenicity, and unclear border, with the aspect ratio > 1 being the most predictive. Huang et al [16] found that the anteroposterior diameter of thyroid nodules > 0.7 cm was statistically significant for differentiation of benign and malignant nodules. Therefore, the apparent hypoechogenicity, unclear border, an aspect ratio > 1, microcalcification and anteroposterior diameter > 0.7 cm are all characteristics that are related to PTMC.…”
Section: Gs-cd-usmentioning
confidence: 99%